Penerapan Metode Multi Objective Optimization on The Basis of Ratio Analysis (MOORA) dalam Penentuan Pembimbing Skripsi Terbaik - Nasution, Aisah Amini; Aldisa, Rima Tamara; Mesran, Mesran; Fadillah, Rizkah (Journal of Information System Research (JOSH), 2024)
The first step in thesis preparation involves titling and selecting a supervisor. Choosing the best supervisors aims to enhance both lecturers' enthusiasm and the quality of student guidance. To identify the most suitable lecturer, thorough consideration and a decision-support system are essential. In this research, the authors employed the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method as a technique integrated into the decision support system. This method aids in determining attribute weight values and the ranking process, ultimately selecting the most favorable supervisor from various available options. From the results of the application of the MOORA method in knowing the best thesis supervisor, namely on alternative A8 with a value of 0.3288 on behalf of Marigan Sianturi, SE, and M.kom,